Participation Role Student in Improving the Quality of Social Studies Learning in Elementary Schools - Wulandari, Tasha (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
The role of student participation has a very important role in improving the quality of Social Sciences learning in elementary schools. This research aims to explore the role of students and improve the quality of social science learning in elementary schools through the application of learning models. This research uses qualitative research methods with a descriptive approach. This approach aims to describe and understand the role of student participation in improving the quality of social science learning in elementary schools. Through interviews, observations and document studies, researchers will obtain in-depth data regarding student involvement in the teaching and learning process. The results of the research show that the application of the learning model significantly increases the role and participation of students in the process of learning social science material in elementary schools. Analysis of learning achievement data also shows a significant increase. The discussion includes an in-depth analysis of the suitability of the learning methods used in relation to the role of students and the role of teachers in it. As well as its impact on improving the quality of social studies learning in elementary schools. Challenges faced, such as choice of method, student motivation, teacher understanding, and availability of resources, are identified and possible solutions are suggested. The implications of this research include recommendations for methods that can be used in the process of increasing students' roles in social science learning in elementary schools and the development of training for teachers to select and implement appropriate learning models.